Association between Brain-Derived Neurotrophic Factor (BDNF) Levels in 2nd Trimester Amniotic Fluid and Fetal Development. (5th December 2018) - Antonakopoulos, Nikolaos; Iliodromiti, Zoe; Mastorakos, George; Iavazzo, Christos; Valsamakis, Georgios; Salakos, Nikolaos; Papageorghiou, Aris; Margeli, Alexandra; Kalantaridou, Sophia; Creatsas, George; Deligeoroglou, Efthymios; Vrachnis, Nikolaos
Abstract : The development of the fetal nervous system mirrors general fetal development, comprising a combination of genetic resources and effects of the intrauterine environment. Our aim was to assess the 2 nd trimester amniotic fluid levels of brain-derived neurotrophic factor (BDNF) and to investigate its association with fetal growth. In accordance with our study design, samples of amniotic fluid were collected from women who had undergone amniocentesis early in the 2 nd trimester. All pregnancies were followed up until delivery and fetal growth patterns and birth weights were recorded, following which pregnancies were divided into three groups based on fetal weight: (1) AGA (appropriate for gestational age), (2) SGA (small for gestational age), and (3) LGA (large for gestational age). We focused on these three groups representing a reflection of the intrauterine growth spectrum. Our results revealed the presence of notably higher BDNF levels in the amniotic fluid of impaired growth fetuses by comparison with those of normal growth. Both SGA and macrosomic fetuses are characterized by notably higher amniotic fluid levels of BDNF (mean values of 36, 300 pg/ml and 35, 700 pg/ml, respectively) compared to normal-growth fetuses (mean value of 32, 700 pg/ml). Though apparently small, this difference is, nevertheless, statistically significant (p value < 0.05) in SGA fetuses in the extremes of the distribution, i.e., below the 3rd centile. In conclusion, there is clear evidence that severe impairment of fetal growth induces the increased production of fetal brain growth factor as an adaptive mechanism in reaction to a hostile intrauterine environment, thereby accelerating fetal brain development and maturation.